Rally round the gun? drug battles and tough on crime candidates in Rio de Janeiro - Lima, Felipe Campos Ronchini (2019)
This thesis studies the effects of violence exposure on electoral outcomes in Rio de Janeiro\'s state legislature elections from 2006 to 2018. By geo-referencing data from anonymous reports, I explore variation across time and space of gun shooting episodes when gangs battle over territories in the city of Rio de Janeiro. The main results indicate that higher exposure to shootings leads to higher vote share for tough-on-crime candidates in areas close to a Pacifying Police Unit (UPP) - a community oriented policing program introduced in 2008. I argue that such program boosted voters\' confidence in law-enforcement and the military as suggested by survey data, benefiting tough-on-crime candidates. I also find null effects on turnout. The results are robust to a number of sensitivity checks and placebo analyses.